High‐resolution barotropic modeling and the calving of the Mertz Glacier, East Antarctica. Issue 10 (15th October 2013) - Mayet, C.; Testut, L.; Legresy, B.; Lescarmontier, L.; Lyard, F.
<x xml:space="preserve">Abstract</x> [1] In February 2010, the Mertz Glacier Tongue (MGT) calved, releasing an 80 × 40 km iceberg. We have developed a high‐resolution barotropic ocean model of the region to simulate the local circulation in response to tides and atmospheric forcing. We improved the coastline, grounding line position and built a new bathymetry using satellite imagery and older bathymetry data to derive the best available tidal model for the region. We compared this and other available models to seven different sea level observations available in the area and significantly improved the tidal solutions reaching a root sum square of 2.3 cm. This model was then run in different bathymetric configurations, considering the ice draft of the major icebergs B9B and C28, to simulate the circulation before, during, and after the calving event. The currents changed substantially in the neighborhood of the MGT and icebergs. The barotropic model with tidal and atmospheric forcing and the atmospheric wind fields allow us to evaluate the forces acting on the MGT. The sea surface slope force dominates the budget. Calving occurred when high tide and strong nontidal currents (due to atmospheric forcing) combined to lead to the monthly maximum forces exerted on the MGT (i.e., between 10 and 13 February 2010). While the forces are not unusually large at the calving time, the currents are largely enhanced in the rifting area. Therefore, processes related to these currents, like melting the ice mélange inside the rifts, should be investigated to fully explain the final stage of the calving.